Alterations and Correlations in Microbial Community and Metabolome Characteristics in Generalized Aggressive Periodontitis - Shi, Meng; Wei, Yiping; Nie, Yong; Wang, Cui; Sun, Fei; Jiang, Wenting; Hu, Wenjie; Wu, Xiaolei (Frontiers in Microbiology, 2020)
This study aimed to characterize the microbial community and metabolic profiles in generalized aggressive periodontitis (AgP) using 16S rRNA gene high-throughput sequencing and gas chromatography-mass spectrometry. A total of 146 subgingival plaque samples and 50 gingival crevicular fluid samples were collected from twenty-four patients with AgP and ten periodontally healthy subjects (PH). Striking differences were observed in subgingival microbiome and gingival crevicular fluid metabolomics between patients with AgP and PH, but not between samples with different probing depths. Metabolomics analysis combined with enrichment analysis revealed that periodontitis significantly altered the concentration of metabolites associated with biosynthesis of amino acids (e.g., alanine, leucine, isoleucine and valine), galactose metabolism (e.g., myo-inositol, galactose, glucose and hexitol) and pyrimidine metabolism (e.g., uracil, uridine, beta alanine and thymine). Correlation analysis showed that the genera with significant difference between AgP and PH were usually significantly correlated with more metabolites, such as Aggregatibacter, Rothia, Peptostreptococcaceae_[XI][G-5], Bacteroidaceae_[G-1]. While glucose and oxoproline had the most significant correlations with microorganisms. Our results revealed distinct microbial communities and metabolic profiles between AgP and PH. The significant correlation between microbial taxa and metabolites suggested the possible mechanisms for periodontitis. Our results also provided effective approaches for detecting periodontal disease and managing periodontitis.